2019
DOI: 10.1111/1742-6723.13282
|View full text |Cite
|
Sign up to set email alerts
|

Can pre‐hospital administration reduce time to initial antibiotic therapy in septic patients?

Abstract: Objective: To quantify the potential time saved with pre-hospital antibiotic therapy in sepsis. Methods: Study data for adult patients transported by Ambulance Victoria (AV), and enrolled into the Australasian Resuscitation In Sepsis Evaluation (ARISE), were linked with pre-hospital electronic records. Results: An AV record was identified for 240 of 341 ARISE patients. The pre-hospital case notes referred to potential infection in 165 patients. The median time to first antibiotic administration from loading th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, among 2,740 patients with sepsis transported by EMS in Alberta between April 2015 and March 2016, the median interval from EMS arrival on scene until ED arrival was 41 minutes and the median time from ED arrival until MD assessment was 44 minutes, a total of 85 minutes (8). Similarly, in the Australasian Resuscitation in Sepsis Evaluation (ARISE) study, the median interval from when EMS reached the patient until they unloaded the stretcher in the ED was 60 minutes, followed by an additional 74 minutes until antibiotics were administered (total 134 min; interquartile range [IQR], 97–182 min) (9). These studies not only highlight the potential opportunity for prehospital administration of antibiotics but also the critical role of the EMS system in early identification and ED prenotification (10).…”
mentioning
confidence: 99%
“…For example, among 2,740 patients with sepsis transported by EMS in Alberta between April 2015 and March 2016, the median interval from EMS arrival on scene until ED arrival was 41 minutes and the median time from ED arrival until MD assessment was 44 minutes, a total of 85 minutes (8). Similarly, in the Australasian Resuscitation in Sepsis Evaluation (ARISE) study, the median interval from when EMS reached the patient until they unloaded the stretcher in the ED was 60 minutes, followed by an additional 74 minutes until antibiotics were administered (total 134 min; interquartile range [IQR], 97–182 min) (9). These studies not only highlight the potential opportunity for prehospital administration of antibiotics but also the critical role of the EMS system in early identification and ED prenotification (10).…”
mentioning
confidence: 99%
“…The recent update of the Surviving Sepsis Campaign: International Guidelines for Management of Sepsis and Septic Shock 2021 (SSC2021) recommended early antibiotic therapy, ideally within 1 to 3 hours of diagnosis of sepsis and within the first hour in cases of septic shock. 4 According to evidence-based medicine, emergency medical services play a crucial role in the delivery of sepsis care bundles [5][6][7][8][9][10] and reducing the time to antibiotic therapy; 7,11,12 however, a recent randomized controlled trial which evaluated the effect of early prehospital antibiotic therapy administration in patients with suspected infection showed negative results in terms of reducing mortality. 13 Nonetheless, several studies have found that prehospital antibiotic administration is associated with lower mortality, particularly in patients with septic shock.…”
Section: Introductionmentioning
confidence: 99%